Analysing Apache Web Logs using Hadoop Cluster - Jothi, R. Anandha; Parthiban, R. (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Today each and every domain have more impact in web. Without web and its applications nothing can be done. In web, the volume of data that are arriving, storing and retrieving is huge. As log files over the web are outsized, storage becomes a limit wherein effective techniques such as virtual database prove to be ineffectual for the same. Based on the, popularity of the products, websites etc. the trend pattern of that particular product or web site is analyzed.Hadoop offers a large scale spread consignment processing infrastructure that provides adequate data storing, distributive and analogous handling, segregation of process and fault tolerant on occurrences of data loss. Here, the semistructured data is practiced using Hadoop. Map reduce algorithm and HDFS (Hadoop Distributed File Systems) are used for analysing of any web site.